Histopatologi Dan Ekspresi TNF-α (Tumor Necrosis Factor-α) Terhadap Kerusakan Hati akibat Invasi Parasit pada Ikan Kembung (Rastrelliger brachysoma) - Allyes Amarens Lekatompessy; Shelly Mieke Pattipeiluhu; Betsy Jane Pattiasina (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Mackerel (Rastrelliger brachysoma) is a type of small pelagic fish lives on the coast and offshore that common infected by parasites. This study aims to identify endoparasits in fish and the effect of the invasion on fish liver tissue through immunohistochemistry technique. The results indicate that there were parasitic agents attack fish livers, including Contracaecum sp and Henneguya sp. The histopathology of liver tissue shows some cells infiltration, cells degeneration and necrosis. The TNF-α expression were positive that was almost all tissue of fish liver infected and cause damage to fish specifically.